2020
DOI: 10.1292/jvms.20-0172
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical phenotyping of macrophages and T lymphocytes infiltrating in peripheral nerve lesions of dourine-affected horses

Abstract: Dourine is a deadly protozoan disease in equids caused by infection with Trypanosoma equiperdum . Neurological signs in the later stage of infection may be caused by peripheral polyneuritis and related axonal degeneration. This neuritis involves T lymphocytes, B lymphocytes, and macrophages, and is observed in cases without obvious neurological signs. However, the pathogenesis of neuritis remains unclear. We identified M2 macrophages and CD8 T cells as the predominant phenotypes in neuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Infected horses manifest various clinical signs, such as edema of the external genitalia, skin plaques, and neurological signs 5 . Pathological examinations of infected horses revealed that these clinical signs are caused by in ammation and edema of the genital organs, dermatitis, and peripheral polyneuritis, respectively [6][7][8][9] . However, the pathogenesis of dourine remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Infected horses manifest various clinical signs, such as edema of the external genitalia, skin plaques, and neurological signs 5 . Pathological examinations of infected horses revealed that these clinical signs are caused by in ammation and edema of the genital organs, dermatitis, and peripheral polyneuritis, respectively [6][7][8][9] . However, the pathogenesis of dourine remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%